PD-1 inhibitors plus nab-paclitaxel-containing chemotherapy for advanced gallbladder cancer in a second-line setting: A retrospective analysis of a case series - Tan, Sirui; Yu, Jing; Huang, Qiyue; Zhou, Nan; Gou, Hongfeng (Frontiers in Oncology, 2022)
Background Gallbladder cancer (GBC) is a fatal cancer, and the efficacy of the current standard second-line chemotherapy for GBC is limited. Novel therapies need to be explored. This retrospective analysis was aimed to investigate the outcomes of patients treated at West China Hospital with PD-1 inhibitors combined with nab-paclitaxel-based chemotherapy (nab-paclitaxel monotherapy or nab-paclitaxel plus other cytotoxic agents) in a second-line setting. Methods Between April 2020 and May 2022, the patients with advanced GBC receiving PD-1 inhibitors combined with nab-paclitaxel-based chemotherapy after resistance to first-line gemcitabine-based chemotherapy at West China Hospital were retrospectively screened. Results Eleven patients were included, and all received gemcitabine-based chemotherapy as first-line therapy. Eight patients underwent next-generation sequencing (NGS), and all had microsatellite stability (MSS) and a low tumor mutation burden (TMB). Six patients were negative for PD-L1 expression and one patient was positive for PD-L1. Therapeutically relevant genetic alterations were not found. All patients received PD-1 inhibitors in combination with nab-paclitaxel-based chemotherapy as second-line therapy. Pembrolizumab was administered in 3 patients, and sintilimab was administered in eight patients. One patient had no measurable target lesion. Complete response (CR) was observed in one (10.0%) patient, partial response (PR) in four (40%) patients, and stable disease (SD) in four (40%) patients. The median progression-free survival (PFS) was 7.5 (95% CI: 2.5-12.5) months, and the median overall survival (OS) was 12.7 (95% CI: 5.5-19.9) months. The adverse events (AEs) were manageable. Conclusion Our results suggest that PD-1 inhibitors combined with nab-paclitaxel-based chemotherapy as second-line therapy for advanced GBC might be a potential treatment and deserves further evaluation.